Answer:
- 8
Step-by-step explanation:
The real problem is that you should asked for the term after the next one.
Given what you have, the next term is likely 2*-4 = -8. That is one way to derive it.
Another would be to start at 0.
y = - 2^(n - 1)
n = 1
- 2^ ( 1-1) = -1 * 2^0
anything to the 0 power = 1 except 0. You cannot have 0^0 power.
Since 2 is not 0 then 2^0= 1
-1*1 = -1
n = 3
-2^(3 - 1) = -2^2 = - 4
Now you can keep on going from there.
I've shown you two ways to get - 8
I think that is your intended answer